Study of Liquid Injectivity in SAG –Foam Process - Sarani, Parisa (IRC, 2014)
Surfactant Alternating Gas (SAG) is an EOR process which involves injection of surfactant and gas alternatively into the reservoir. Different type of gas has been used in SAG injection; however the selection of gas is normally based on its availability and economic considerations. Only few studies are conducted to study the liquid injectivity in SAG-Foam process. Thus, the project is conducted to study CO2 as the gas used in SAG process to generate the foam in the reservoir. Foam injection is used as an EOR method to help the reduction of gas mobility in the reservoir. High mobility of the gas in the reservoir may cause gravity override and early breakthrough of the injected gas. This project involves simulation study using reservoir model constructed with reservoir data obtained from the literature. A preliminary study has been conducted to study the behavior of the liquid injectivity in homogeneous reservoir. More comprehensive study is required to fully understand and validate the result. Future project work includes generation of reservoir model and simulation of SAG- foam parameters to study the liquid injectivity and foam propagation behavior in the reservoir.